EVALUASI PROGRAM DESAIN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM MELALUI MODEL CONTEXT, INPUT, PROCESS, PRODUCT (CIPP) - amalina, nur (Institut Agama Islam Negeri (IAIN) Palopo, 2019)
This study aims to determine aspects of context, input, process and product Islamic Instructional Design in SMAN 4 Palopo. This study is a qualitative research. The approach was management. Analysis of the data used were descriptive analysis by performing data reduction, data presentation, and conclusion. The results of this study indicate that: (1) According to context, form of Islamic instructional design used was a curriculum-based learning design in 2013 formulated individually. The teachers' qualifications were accordance with the educational background and pedagogical competence of some teachers was still less than the maximum, and supporting factors were computer, papers, and printer. (2) According to input, the support of school and effort of the teachers was still less than the maximum. (3) According to process, the suitability of the utilization of the Islamic instructional design was sometimes appropriate and sometimes not appropriate. The time of making the Islamic instructional design conducted beginning of each semester, although sometimes the Islamic instructional design has not finished and the period of utilization of the Islamic instructional design was for one semester. (4) According to product, the impact of the utilization of the Islamic instructional design have positive impacts and negative impacts, and the students' responses to the utilization of the Islamic instructional design have positive response and negative response.